KUALITAS MIKROBIOlOGI UDARA DI RUANG RAWAT INAP PENYAKIT MENULAR 01 RUMAH SAKlT PARU SURABAYATAHUN 2012 - Kiki Ayu Pratiwi; Rachmaniyah .; Erna Triastuti (Poltekkes Kemenkes Surabaya, 2013)
Surabaya Lung Hospital is one of health care institutions classified as Special Hospital that providesprimary care to a field or against certain type of disease. In the space of infectious disease hospitalization hasnot been done since the establishment of air quality inspections ward inpatient hospitalization so that thespace of potentially infectious diseases as a cause of infection among patients with officers Silang, patientswith medical equipment and patient with visitors. The objective of the research was to examine themicrobiological air quality in the treatment ward for infectious disease at Surabaya Paru Hospital 2012.This was a descriptive study, conducted in May 2012, collecting data from observations, interviews, fieldmeasurements, and laboratory tests. Data were subsequently analyzed descriptively, with reference todesignations in the Ministry of Health Republic of Indonesia/Menkes/SK/X/2004 on the requirementspertaining to Hospital's Enviromental Health.The result indicated that the total number of microorganisms in the treatment ward for infectiousdiseaseswas 1860 CFU/m3 by category It was classified as non-compliance, level of lighting was 44.1 lux andconsidered non-compliance, air velocity was 0.53 m / DKT which was in compliance, temperaturemeasurement resulted in non-compliance figure of 25°C, humidity was 77% that means a non-compliance,assessment of building maintenance process in treatment ward for infectious diseases resulted in apercentage of 66.6% that was In compliance, While in terms of Construction the percentage was 55% thatmeans it was not in compliance.Based on these results, the study find it necessary to improve cleaning services in order to makeimprovements in accordance with the SOP(Standard Operating Procedure) which applicable and preferably toIPS (Installation of infrastructure and fadlities) non-medical need such as the improvement of buildingconstruction that needsto be improved.Keywords: microbiological air quality, infectlous diseas